Komponen utama gaji kehidupan wajar - Mohd Arshad, Mohd Nahar (IKIM, 2019)
The objective of this article is to understand the main components of living wage. The assessment of the determination of wage through the market mechanism is first discussed. It is argued that the valuation of living wage via the labor market mechanism alone is not sufficient. Thus, the estimation of living wage needs to take into account religious and cultural elements since living wage components include the normative understanding of such concepts as fair wage, equitable wage, deserving wage and decent wage. At the same time, the estimation of living wage requires consultation and feedback from employers, workers, labour union and policy-makers. Issues pertaining to the implementation of living wage are also discussed in this article.